(untitled) (Journal of Philosophy Culture and Political Science, 2025)
This article explores the concept of "Niyet" (Intention) in Kazakh society from a philosophical and social perspective. The study examines the role of intention in traditional Kazakh worldview, highlighting its significance as an indicator of human purity and moral values. Furthermore, it analyzes how the epistemology of intention forms the foundation of national culture, philosophy, and ethics. The article takes into account the views of President of Kazakhstan, Kassym-Jomart Tokayev, on the modernization of public consciousness, emphasizing the close connection between state reforms and the concept of intention. The moral and spiritual importance of intention is discussed, along with its motivational role in human actions. The study also examines the concept of intention in the legacy of Kazakh biys (judges) and orators, emphasizing its fundamental role in justice and integrity. References are made to the works of Abai, Shakarim, Yusuf Balasaguni, and Ahmed Yasawi, demonstrating the deep connection between intention and both inner human spirituality and social life. The study distinguishes between positive and negative types of intention, proving its role as a key factor in societal development and stability. From an Islamic perspective, the article also analyzes the spiritual and religious significance of intention. In conclusion, the article highlights the social, cultural, and philosophical importance of the concept of intention, proving its relevance in modern society. Keywords: Kazakh worldview, intention, morality and ethics, public consciousness, spiritual values, societal development, presidential reforms.